Advantages of Introducing Quality Management System in Textile Companies of the Republic - Raxmonov F.A. (Zien Journals, 2022)
In this article, there is a wide range of processes for the production of modern materials for the recycling of waste derived from industrial waste, metallurgy, oral cavity, chemical technology, mining, q beating materials, wood and other industrial waste data is highlighted
Keywords: liberalization; modernization; qurilish industry; engineering and communication